2.4: Improving Picture‐reproducing Quality by a New Color Gamut Mapping Method. (24th February 2021) - Xia, Daxue; Chen, Lin; Xie, Renli
Abstract : The color gamut of input source and the display set usually are disparate, therefore, a mapping mechanism between them is necessary and makes significant impact on the picture reproducing quality. In this paper, a new gamut mapping algorithm is proposed, which reduces color difference significantly between the source and target, compared with that without adopting such mapping process. The gamma behavior of luminance dependence on gray scale has been little affected. Artifacts like saturation inversion and hue inconsistency are avoided.